Isolasi Bakteri Endofit Balakacida (Chromolaena odorata) Asal Banda Aceh dan Uji Aktivitas Antimikroba terhadap Bakteri Patogen Pasteurella multocida dan Bacillus subtilis - Wahyu Eka Sari; Darmawi Darmawi; Rumi Sahara Zamzami; Henni Vanda; Nurliana Nurliana; Etriwati Etriwati; Luthfia Amanda (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Endophytic bacteria are bacteria that live in plant tissue without causing negative effects. Endophytic bacteria can produce bioactive compounds that can be used as antibacterial, anti-fungal, antiviral, anti-cancer, anti-diabetic, antimalarial and anti-immunosuppressive properties. Endophytic bacteria are found in all higher plants, one of which is balakacida (Chromolaena odorata). This study aims to isolate the endophytic bacteria balakacida plant from Banda Aceh, to test the antimicrobial activity against the pathogenic bacteria Pasteurella multocida and Bacillus subtilis. The samples used were young leaves of balakacida plant with the method of isolation and purification of endophytic bacteria and in vitro tests.The results showed that endophytic bacteria could be isolated from balakacida plant and showed inhibitory activity against the pathogenic bacteria Pasteurella multocida and Bacillus subtilis. Thus, the endophytic bacteria from balakacida have bioactive compounds that have potential as antimicrobials.